2015
DOI: 10.1111/fwb.12588
|View full text |Cite
|
Sign up to set email alerts
|

Substratum‐dependent responses of ciliate assemblages to temperature: a natural experiment in Icelandic streams

Abstract: 1. Ciliate assemblages play a significant role in the microbial food web. The effects of environmental temperature on assemblage composition may be influenced by abiotic factors such as seasonality and disturbance, but the effects of temperature on ciliate assemblages found on different substrata have not been explored. Sandy bottoms and submerged rocks harbour dissimilar ciliate assemblages, and it might be expected that their ciliate assemblages will respond differently to temperature. 2. We studied how alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…The distribution of ciliate assemblages throughout the water column may also be affected by temperature, which decreases with depth (range 5-23°C). The pattern we observe is consistent with a morphological study on the influence of temperature on benthic ciliates in freshwater environments with rocky substrates (Plebani et al 2015) and a molecular study of oligotrichs and choreotrichs along an estuarine salinity gradient .…”
Section: Abiotic Factorssupporting
confidence: 90%
See 2 more Smart Citations
“…The distribution of ciliate assemblages throughout the water column may also be affected by temperature, which decreases with depth (range 5-23°C). The pattern we observe is consistent with a morphological study on the influence of temperature on benthic ciliates in freshwater environments with rocky substrates (Plebani et al 2015) and a molecular study of oligotrichs and choreotrichs along an estuarine salinity gradient .…”
Section: Abiotic Factorssupporting
confidence: 90%
“…The pattern we observe is consistent with a morphological study on the influence of temperature on benthic ciliates in freshwater environments with rocky substrates (Plebani et al . ) and a molecular study of oligotrichs and choreotrichs along an estuarine salinity gradient (Tamura et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implications of coalescence for natural community structure and function is unclear, but could be particularly important in the context of environmental change [97]. Temperature changes alter eco-evolutionary dynamics, and could impact coalescence through range shifts, altering species interactions, and changing weather patterns [97][98][99][100]. Additionally, antibiotics and environmental pollutants disturb gut, soil and aquatic microbiomes with associated disease outbreaks and biodiversity loss [101][102][103].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work on aquatic biofilms developed under different thermal regimes has shown that modest temperature increases of the order of 2-58C can have considerable effects on the development, structure and functioning of communities comprising bacteria and other single-celled organisms [3,38,[46][47][48]. Several studies have shown positive effects of warming, in that biofilms develop more quickly at elevated temperatures [3,47,49], while other studies have documented changes in the relative abundances of bacteria and protists [38,46,50].…”
Section: Discussionmentioning
confidence: 99%